Pengaruh Sistem Administrasi Perpajakan Modern dan Sanksi Perpajakan Pada Kepatuhan Wajib Pajak Orang Pribadi - Surya Puspita Dewi, Ni Luh Putu Dessy; Setiawan, Putu Ery (E-Jurnal Akuntansi; Vol 21 No 3 (2017)DO - 10.24843/EJA.2017.v21.i03.p05, 2017)
Modern tax administration is a process of renewal is a priority tax reform that includes the field of organizational structure, business processes and information technology and communications, human resource management and good governance as an effort to increase tax revenues through increased tax compliance.In addition to the system of tax administration, tax penalties is one of the factors that affect the level of tax compliance.The aim of this study was to determine the influence of modern tax administration system and tax penalties on the individual taxpayer compliance in KPP Pratama Badung Selatan.T he samples used were 100 individual taxpayer with accidental sampling technique.The data analysis technique used is multiple linear regression analysis. The results show that there are positive influence of modern tax administration system and tax penalties on the individual taxpayer compliance in KPP Pratama Badung Selatan.
Keywords: modern tax administration system, tax penalties, tax compliance